Fructan metabolism and changes in fructan composition during cold acclimation in perennial ryegrass - Abeynayake, Shamila W.; Etzerodt, Thomas P.; Jonavičienė, Kristina; Byrne, Stephen; Asp, Torben; Boelt, Birte (Frontiers in Plant Science, 2015)
Perennial ryegrass (Lolium perenne L.) produces high levels of fructans as a mixture of oligomers with different degrees of polymerization (DP). The present study describes the analysis of the compositional changes in the full spectrum of fructan oligomers, fructan distribution between above ground biomass (top) and the roots, and the transcription of candidate genes involved in fructan metabolism during cold acclimation in perennial ryegrass variety ‘Veyo’ and ecotype ‘Falster’ from distinct geographical origins. We observed changes in fructan composition and induction of low-DP fructans, especially DP=4, in both the top and the roots of ‘Veyo’ and ‘Falster’ in response to low-temperature stress. The accumulation of fructans, DP˃50 was only apparent in the top tissues where the Lp1-FFT expression is higher compared to the roots in both “Veyo” and “Falster. Our results also show the accumulation and depolymerization of fructans with different DP, together with the induction of genes encoding fructosyltransferases and fructan exohydrolases in both ‘Veyo’ and ‘Falster’ during cold acclimation, supporting the hypothesis that fructan synthesis and depolymerization occurring simultaneously. The ecotype ‘Falster’, adapted to cold climates, increased total fructan content and produced more fructans (DP˃7) in the roots than the variety ‘Veyo’, adapted to warmer climates suggesting that accumulation of fructans in roots, especially the high-DP fructans as an adaptive trait for plant recovery after abiotic stresses.